Chlamydia pneumoniae and progression of subclinical atherosclerosis. (May 2014) - Player, Marty S; Mainous, Arch G; Everett, Charles J; Diaz, Vanessa A; Knoll, Michele E; Wright, Robert U
Background: Cross-sectional investigation between presence of antibodies and coronary artery calcification (CAC) in past studies has shown no relationship, but progression over time has not been investigated. The objective of this study was to determine the relationship between presence of Chlamydia pneumoniae antibodies and progression of CAC and ankle–brachial index (ABI). Design: The Multiethnic Study of Atherosclerosis (MESA) is a prospective population-based cohort of racially and ethnically diverse male and female participants recruited from six communities in the USA, age 45–84 years, free of clinical cardiovascular disease at baseline. Methods: The main outcomes were progression of mean CAC and ABI between exams 1 (2000–02) and 3 (2004–05) (median follow-up of 3.13 years) by C. pneumoniae antibody. Multivariate models adjusting for demographics, obesity, smoking, alcohol use, and physical activity were computed. Results: Of 2223 subjects analysed, 76% were positive for C. pneumoniae antibodies. Progression of CAC was significantly higher in the antibody-positive group (93.8 vs. 78.2 agatston units, p  = 0.02) and in antibody-positive subjects with CAC ≥10 at baseline (216.5 vs. 178.6, p  = 0.02) than antibody-negative group. Smoking and body mass index ≥30 kg/m 2 both had interactions with presence of C. pneumoniae yielding significantly greater CAC progression. Progression of ABI did not significantly differ by C. pneumoniae antibody status in models adjusted for covariates. Conclusions: C. pneumoniae antibodies are related to progression of CAC, particularly in individuals with CAC present at baseline. This provides evidence that certain groups are at higher risk of atherosclerotic progression and may be useful for risk stratification and treatment.